2015
DOI: 10.1111/jsr.12334
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence and characteristics of obstructive sleep apnea in hospitalized patients with type 2 diabetes in China

Abstract: SUMMARYData on the prevalence of obstructive sleep apnea in subjects with type 2 diabetes mellitus in China is scarce. We conducted a multi-centre, cross-sectional study involving 12 hospitals from six regional cities to investigate the prevalence of obstructive sleep apnea in hospitalized patients with type 2 diabetes mellitus and to explore the association between obstructive sleep apnea and related risk factors, diabetic complications and comorbidities in China. Each hospital recruited at least 70 consecuti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
60
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(71 citation statements)
references
References 31 publications
9
60
1
1
Order By: Relevance
“…Yet, unlike this previous study , we excluded patients with painful DPN (i.e. we only included painless DPN in those groups with DPN) or sleep apnoea, which are known to negatively impact on sleep , and their exclusion may explain why we did not find any daily sleep differences .…”
Section: Discussionmentioning
confidence: 99%
“…Yet, unlike this previous study , we excluded patients with painful DPN (i.e. we only included painless DPN in those groups with DPN) or sleep apnoea, which are known to negatively impact on sleep , and their exclusion may explain why we did not find any daily sleep differences .…”
Section: Discussionmentioning
confidence: 99%
“…Despite the fact that a higher number of persons with OSA is recorded, because of the nonspecific symptoms, the non-diagnosis percentage is further increased (70-80%) [11].…”
Section: Osa Prevalence and Its Risk Factorsmentioning
confidence: 99%
“…In a study conducted by Zhang P. et al in China on a group of 880 subjects with type 2 diabetes, it was found a high overall prevalence of OSA (60%) and of moderate-severe OSA (25.6%) [11].…”
Section: Osa and Type 2 Diabetes Mellitusmentioning
confidence: 99%
See 2 more Smart Citations